MENILAI DAYA TARIK PROGRAM STUDI BAHASA JEPANG: PENGARUH KUALITAS PENDIDIKAN DAN BRAND IMAGE TERHADAP NIAT PENDAFTARAN MAHASISWA DI UNIVERSITAS WIDYATAMA - Akbar, Tri Sanatha Wahyu (PT Naureen Digital Education, 2025)
This study aims to assess the quality of education in the Japanese Language Diploma Program (D3) at Universitas Widyatama, evaluate the program's brand image, and analyze the impact of both quality of education and brand image on prospective students' intention to enroll in the program. The research employs a descriptive-analytical and verificative approach. The descriptive aspect seeks to illustrate how the quality of education and brand image influence prospective students' interest in enrolling, while the verificative aspect examines the direct effect of education quality and brand image on the enrollment intentions of third-year high school (SMA/SMK) students. Data were collected through a survey with a sample of 100 respondents, comprising third-year high school/ vocational school students and alumni who had been exposed to promotional efforts by the UTama Marketing Bureau and the Japanese Language Program. The results of the F-test indicate that both education quality and brand image have a significant combined impact on prospective students' enrollment intentions for the D3 Japanese Language Program at Universitas Widyatama, with an R-Square coefficient of 0.281, or 28.1%. This means that education quality and brand image together explain 28.1% of the variability in students' intention to enroll, while the remaining 71.9% is influenced by other factors not covered in this study, such as social, economic, or personal preferences. The findings provide insight into the factors influencing prospective students' decisions to choose the D3 Japanese Language Program at Universitas Widyatama. Keywords: Brand image, Education Quality, Enrollment Intention.